Banks' foreign claims in the aftermath of the 2008 crisis: Institutional response, financial efficiency, and integration of cross-border banking in the Euro area - Thierry Warin; Aleksandar Stojkov (Journal of Risk and Financial Management, 2021)
Beyond financial stability as the European Banking Union's primary objective, the European capital market integration provides an impetus for deepening bank integration and greater financial market efficiency. This article proposes an empirical framework to assess the dynamics of euro area banks' business networking. We use banks' foreign claims across Europe, particularly the euro area, to see how banks react to various macroeconomic signals. Banks' foreign claims are particularly interesting due to their sensitivity. One of the main conclusions is that the euro area has seen a reallocation of capital in the aftermath of the 2008 crisis. The financial picture of Europe is different after the recent financial crisis. Although we observe a re-concentration of capital from the periphery to the core countries, we also observe some signs of recovered confidence within the European banking framework for macro-prudential reasons.
Keywords: E5; G1; G2; 330; banking industry; capital flows; financial regulation